Time Trends in Medically Serious Suicide-Related Behaviours in Boys and Girls. (October 2014) - Rhodes, Anne E; Lu, Hong; Skinner, Robin
Objective: To determine whether emergency department (ED) presentations for suicide-related behaviours (SRBs) in boys and girls were identified as more clinically acute in the ED in the period after the regulatory warnings against prescribing antidepressants and during the global economic recession, and to characterize the medical severity of SRBs among boys and girls to aid surveillance activities. Method: Among Ontario boys and girls (aged 12 to 17 years) presenting to the ED with an incident (index) ED SRB event between fiscal years (FYs) 2002 to 2010, we compared the number of high (compared with lower) acuity events in FYs 2005 to 2010 to those in FYs 2002 to 2004. We described the SRB method by its acuity and tested the linearity of varying trends in the SRB method in boys and girls. Results: In both boys and girls, high acuity events were 50% greater after FY 2004 than before, regardless of subsequent admission, and most common among boys and girls who self-poisoned. In girls, opposing linear trends before and after FY 2004 were observed in the proportion of self-poisonings and cut (or) pierce SRB methods. Throughout the study period, there was a linear decline in the proportion of boys presenting to the ED with other methods. Conclusions: The previously reported increase in hospital admissions after the warnings and during the recession is unlikely artifactual. An equivalent increase in high acuity events was also evident among those not subsequently admitted. The reasons for varying responses in boys and girls by SRB method warrant further study.